L’assurance de responsablité civile, cette incomprise : les conséquences de travaux mal faits sont-ils assurables ? - Moreau, Rémi (Assurances, 1995)
This article deals with a warranty suit in which an insurer unsuccessfully attempted to deny coverage, under a CGL policy, for an exclusion which applies to damage to impaired property or property not physically injured. The plaintiff alleges economic losses due to faulty workmanship. The court found that there was a duty to defend the plaintiff and to pay the costs of repairing as determined by the principal action. The author disagrees and attempts to explain that the CGL policy, unlike a performance bond, is not intended to cover costs associated with repairing or replacing the insured's defective work, which is purely an economic loss.